Establishing a relationship between semen evaluation parameters of freezable and non-freezable Murrah buffalo bull semen - YOGITA DHAKAR; MADHUMEET SINGH; AKSHAY SHARMA; PRAVESH KUMAR (Indian Journal of Animal Sciences, 2021)
The present study was conducted with an objective of establishing a relationship between semen evaluation parameters of freezable and non-freezable Murrah buffalo semen. Work was conducted at Frozen Semen Bank, RCDF Limited, Bassi, Jaipur, Rajasthan, on 12 apparently healthy pure bred Murrah buffalo breeding bulls. A total of 96 ejaculates (48 each freezable and non-freezable) were analysed at five different stages of processing namely neat semen evaluation, post dilution, post equilibration, post thaw and after 1 h of incubation post-thaw at 37°C for progressive motility, live dead count, reaction to hypo-osmotic solution and acrosomal integrity. Evaluation of the semen was done in two groups, i.e. freezable and non-freezable semen. There was a significant difference in terms of all the semen evaluation parameters between freezable and non-freezable semen at different stages of evaluation. Also, results of the study revealed a highly significant correlation between the various semen evaluation parameters for both the groups.